PENGARUH KEPEMIMPINAN MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PT. LPI - Novitasari Novitasari (Jurnal Signaling, 2018)
This study aims to examine the effect of Motivational Leadership and Job Satisfaction on the Performance of employees of PT. LPI. To determine the effect of Motivational Leadership on the Performance of employees of PT. LPI. To determine the effect of Job Satisfaction on the Performance of employees of PT. LPI. To find out which variable is the most dominant influence on the performance of employees of PT. LPI. The result of testing the equation Y in hypothesis 1 shows that the significance value of the leadership variable (X1) is 0.733 which means that the model is not significant because the significance is 0.05. Thus Ha is rejected and Ho is accepted. Therefore, it can be interpreted that leadership has no positive and significant effect on employee performance. Hypothesis 2 shows that motivation and job satisfaction (X2) amounted to .000 so that it can be said that this model is significant because the significance is 0.05. Thus, Ho is rejected and Ha is accepted. This can be interpreted that work motivation has a significant effect on employee performance. Hypothesis 3 job satisfaction (X3) of 0.456 so that it can be said that this model is not significant because of the significance 0.05. Thus, Ho is accepted and Ha is rejected. This can be interpreted that job satisfaction is influential significant on employee performance. F test results with 0.0001 significance the probability is smaller than 0.05 then the regression model can be used for predict employee performance (Y). This shows that the influence of leadership, work motivation, and job satisfaction simultaneously affect the performance of employees of PT. LPI.